Preparation method of high thermal conductive epoxy composite insulating material based on diamond filling
Patent Information
- Application Number
- CN202311766255.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-19
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-12-19
AI Technical Summary
[0009]针对现有技术的不足,本发明提供了一种基于金刚石填充的高导热环氧复合绝缘材料制备方法,解决了现有技术中表面改性金刚石充填环氧绝缘材料时存在产生“三废”污染的技术问题
[0035]本发明通过调控促进剂的催化活性与加料工序,以改变环氧树脂基体的交联固化反应速率与流变特性,同时结合多元异质填料复配的协同方法,有效提高了填料的堆积密度,并降低了树脂基体与高密度无机填料间的本征密度差,继而实现了对高密度金刚石在环氧树脂中沉降的抑制,使得所获环氧绝缘材料的绝缘、耐热、机械和导热等多维性能均有显著提升。
Smart Images

Figure CN117700937B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of insulating materials technology, and specifically to a method for preparing a diamond-filled high thermal conductivity epoxy composite insulating material. Background Technology
[0002] Because of its excellent insulation, mechanical, and chemical stability, epoxy resin cured products have long been used as the main insulating material in processes such as electronic device packaging and electrical equipment manufacturing. However, with the rapid development of electronic devices towards miniaturization and high integration density, the heat generated per unit volume of electronic devices has increased dramatically. The temperature rise caused by the accumulation of internal heat will accelerate the aging and failure of epoxy insulation materials.
[0003] Existing research indicates that the lifespan of electronic devices decreases exponentially with increasing temperature, severely impacting their safety and reliability. Therefore, there is an urgent need to develop epoxy insulation materials with high thermal conductivity to accelerate heat conduction within devices, reduce heat buildup, and thus address the aforementioned problems.
[0004] Diamond possesses extremely high thermal conductivity (1000–2000 W / m·K) and extremely low coefficient of thermal expansion (2 × 10⁻⁶ K⁻¹), making micron-sized diamond a highly valuable high-thermal-conductivity inorganic filler. Filling epoxy resin with highly thermally conductive diamond fillers is an effective method to enhance the thermal conductivity of materials. For example, Chinese Patent Publication No. CN 106752645A discloses a nanodiamond heat-dissipating, energy-saving, and environmentally friendly thin-film coating, the prepared nanodiamond heat-dissipating coating exhibiting excellent heat dissipation and adhesion properties.
[0005] However, the addition of graphene oxide and fibrous carbon powder to the above coating reduces the insulation resistance of the resulting film, making it difficult to apply to electronic device packaging in high-insulation environments. Furthermore, this heat-dissipating coating only enhances the surface heat dissipation of electronic components and cannot fundamentally solve the problems of heat accumulation and conduction difficulties within the electronic devices.
[0006] Furthermore, when diamond is used as a thermally conductive reinforcing filler in epoxy resin, it also presents the problem of insulation performance degradation caused by filler sedimentation. On the one hand, it leads to the deterioration of the material's processing performance, specifically, the viscosity of the composite material at the filler sedimentation points increases significantly. Uneven dispersion caused by filler sedimentation also results in significant differences in curing shrinkage stress at different locations during molding, easily leading to molding defects or stress cracking. On the other hand, due to the difference in dielectric constants between the resin and the filler, filler aggregation within the resin matrix also causes distortion of the electric field distribution on the material surface. The electric field distribution is more concentrated at the filler-resin matrix interface, becoming a weak point in the epoxy material's insulation, thus increasing the risk of insulation failure.
[0007] To overcome the aforementioned shortcomings, some existing technologies have proposed methods to enhance the bonding force between the resin matrix and the filler heterogeneous interface by modifying the filler surface, thereby promoting the dispersion of inorganic fillers within the resin matrix and inhibiting filler sedimentation. For example, Chinese Patent Publication No. CN 107446308 A discloses a nanodiamond surface modification technology using a gas-phase oxidation method followed by liquid-phase modification. However, due to the chemical inertness of the diamond surface, strong oxidants or strong acid / base modifiers must be used during the surface modification process, resulting in environmental pollution from the generated waste.
[0008] Therefore, there is an urgent need to provide a method for preparing diamond-filled high thermal conductivity epoxy composite insulation materials to solve the environmental pollution problem caused by surface modification of diamond in the preparation of diamond-filled epoxy insulation materials in the existing technology, so as to obtain diamond-filled epoxy composite insulation materials with high thermal conductivity. Summary of the Invention
[0009] To address the shortcomings of existing technologies, this invention provides a method for preparing a diamond-filled high thermal conductivity epoxy composite insulating material, which solves the technical problem of generating "three wastes" pollution when surface-modified diamond-filled epoxy insulating materials are used in existing technologies.
[0010] To achieve the above objectives, the present invention provides the following technical solution:
[0011] This invention provides a method for preparing a diamond-filled high thermal conductivity epoxy composite insulating material, the method comprising:
[0012] Prepare the following by weight percentage: 15-20% epoxy resin, 8-12% curing agent, 0.1-0.12% accelerator, 20-30% SiO2, 15-35% silica powder, 5-20% diamond, 1-10% light calcium carbonate and 1-5% wollastonite.
[0013] Purified diamond, SiO2, silica powder, light calcium carbonate, and wollastonite were obtained respectively.
[0014] Obtaining the organic phase: Place epoxy resin, curing agent and part of the accelerator in a reaction vessel, heat and stir at a uniform speed to obtain a homogeneous organic phase;
[0015] Obtaining the mixed phase: Purified SiO2, silica powder, light calcium carbonate and wollastonite are added to the reactor in the set order and speed, heated and stirred at a uniform speed to obtain a homogeneous mixed phase;
[0016] Obtaining the target composite phase: Purified diamond is added to the mixed phase at a set rate, heated and stirred at a uniform speed to obtain a homogeneous composite phase, and then subjected to initial vacuum degassing. After vacuum degassing is completed, the remaining accelerator is added to the composite phase, and a second vacuum degassing is performed to obtain the target composite phase.
[0017] The target composite phase is vacuum cast and then cured in stages. After demolding, the target product is obtained.
[0018] Furthermore, the process of obtaining purified diamond powder, SiO2 powder, silica powder, light calcium carbonate powder, and wollastonite powder includes:
[0019] Prepare five containers, each containing a mixed solution of ethanol and tetrahydrofuran;
[0020] Diamond, SiO2, silica powder, light calcium carbonate, and wollastonite are each placed in one of the containers.
[0021] Each container is subjected to reflux at a temperature of 60–80°C for 3–8 hours, during which the mixture in the container is stirred at a constant speed of 100–300 rpm. After reflux, solid-liquid phase separation is performed, and the separated material is placed in a constant temperature oven for continuous drying at a temperature of 60–150°C for 24–36 hours until the separated material particles are distinct, do not accumulate or adhere.
[0022] The purified diamond powder, SiO2 powder, silica powder, light calcium carbonate powder, and wollastonite powder were obtained.
[0023] Furthermore, the step of placing epoxy resin, curing agent, and a portion of accelerator in a reaction vessel, heating and stirring at a uniform speed to obtain a homogeneous organic phase specifically involves:
[0024] Epoxy resin, curing agent, and accelerator accounting for 0.03% to 0.06% of the total mass of the target product are placed in a reaction vessel and heated at a temperature of 60 to 100°C and a speed of 100 to 300 rpm with uniform stirring to obtain a homogeneous organic phase.
[0025] Furthermore, the specific order of feeding SiO2, silica powder, light calcium carbonate and wollastonite during the process of obtaining the mixed phase is as follows: light calcium carbonate, SiO2, silica powder, wollastonite, and the feeding rate of light calcium carbonate, SiO2, silica powder and wollastonite is 5-15 g / min.
[0026] Furthermore, during the process of obtaining the mixed phase and the target composite phase, the heating and uniform stirring conditions are as follows: heating temperature is 50-70℃, and stirring speed is 500-800rpm.
[0027] Furthermore, the vacuum degree of both the primary and secondary vacuum degassing is 0.08–0.1 MPa, with the primary vacuum degassing lasting 0.5–1 h and the secondary vacuum degassing lasting 5–10 min.
[0028] Furthermore, the vacuum casting conditions are: vacuum degree of 0.08-0.1 MPa, vacuum casting temperature of 60-100℃; the step curing is specifically: curing at 60-100℃ for 2-6 hours, then curing at 80-140℃ for 4-8 hours, and finally curing at 100-160℃ for 6-18 hours.
[0029] Furthermore, the diamond feeding rate during the acquisition of the target composite phase is 2–6 g / min.
[0030] Furthermore, the average particle size of SiO2, silicon micro powder and diamond is 10-20 μm, the average particle size of light calcium carbonate is 3-6 μm, and the average particle size of wollastonite is 10-38 μm with an aspect ratio of 10:1.
[0031] Furthermore, the epoxy resin matrix is one or more of glycidyl ethers, glycidyl esters, glycidyl amines, linear aliphatic resins, and alicyclic resins;
[0032] The curing agent is one or more of amine curing agents, acid anhydride curing agents, and latent curing agents;
[0033] The accelerator is one or more of amines, phenols, and boron trifluoride complexes.
[0034] The present invention provides a method for preparing a diamond-filled high thermal conductivity epoxy composite insulating material, which has the following advantages compared with the prior art:
[0035] This invention modifies the crosslinking and curing reaction rate and rheological properties of the epoxy resin matrix by controlling the catalytic activity of the accelerator and the feeding process. At the same time, it combines a synergistic method of compounding multiple heterogeneous fillers to effectively improve the packing density of the fillers and reduce the intrinsic density difference between the resin matrix and the high-density inorganic fillers. This, in turn, suppresses the sedimentation of high-density diamond in the epoxy resin, resulting in a significant improvement in the insulation, heat resistance, mechanical properties, and thermal conductivity of the obtained epoxy insulation material.
[0036] The present invention selects SiO2, silica powder, light calcium carbonate and wollastonite as inorganic reinforcing fillers, which have the characteristics of high density and low oil absorption. While ensuring the process performance of epoxy materials, it can improve the dispersion effect of multi-component heterogeneous fillers in epoxy resin, avoid the problem of electric field distortion caused by filler agglomeration in resin under high electric field strength, and thus reduce the risk of insulation breakdown of epoxy insulation materials.
[0037] This invention does not involve additional surface organic modification of the multi-component heterogeneous filler, which not only reduces environmental pollution caused by strong acid, strong alkali and strong oxidant treatment of the filler surface; at the same time, the simplification of the filler purification, compounding and composite material preparation process makes it easier to meet the requirements of industrial scale-up production, and greatly enhances the potential application value of this technology. Attached Figure Description
[0038] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0039] Figure 1 Scanning electron microscope image of the epoxy composite insulation material with multi-component heterogeneous fillers obtained in Example 1;
[0040] Figure 2 A comparison graph showing the thermal conductivity of the samples obtained in Example 1, Comparative Example 1, and Comparative Example 2;
[0041] Figure 3 This is a comparison chart of the AC breakdown strength of the samples obtained in Example 1, Comparative Example 1, and Comparative Example 2 under power frequency.
[0042] Figure 4 This is a comparison diagram of the AC breakdown strength of the samples obtained under the feeding sequence ①, ②, and ③ in Comparative Example 3 and the sample obtained in Example 1 at the power frequency.
[0043] Figure 5 This is a comparison chart of the glass transition temperatures of the samples obtained in Example 1, Comparative Example 1, and Comparative Example 2;
[0044] Figure 6 Comparison diagram of bending strength of samples obtained in Example 1, Comparative Example 1 and Comparative Example 2;
[0045] Figure 7 This is a comparison diagram of the bending strength of the samples obtained under the feeding sequence of ①, ②, and ③ in Comparative Example 3 and the sample obtained in Example 1;
[0046] Figure 8 This is a comparison diagram of the power frequency dielectric loss of the samples obtained in Example 1, Comparative Example 1, and Comparative Example 2;
[0047] Figure 9 This is a comparison graph of the viscosity-time curves of the samples obtained in Example 1 and Comparative Example 1 at 80°C.
[0048] Figure 10This is a comparison chart of the viscosity-time curves of epoxy composite insulating materials corresponding to different types of accelerators in Comparative Example 4 of this invention (①, ②, and ③).
[0049] Figure 11 Comparison diagrams of the bending strength of the samples obtained in Examples 1-5;
[0050] Figure 12 Comparison of AC breakdown strength at power frequency for samples obtained in Examples 2-5;
[0051] Figure 13 The diagram shows a comparison of the bending strength of the samples obtained in Examples 1 to 7. Detailed Implementation
[0052] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0053] To overcome the limitations of existing technologies that use gas-phase oxidation followed by liquid-phase modification to modify nanodiamond surfaces for use as thermally conductive reinforcing fillers in epoxy resins, which are only suitable for high specific surface area nano-sized diamonds, and whose chemical inertness necessitates the use of strong oxidants or strong acid / base modifiers during surface modification, thus generating waste and exacerbating environmental pollution, the main approach of this application is as follows:
[0054] To address the epoxy insulation materials required for power equipment and electronic devices in high-insulation scenarios, this paper proposes a method that combines the regulation of the epoxy resin crosslinking and curing reaction process with the synergistic effect of compounding with multi-component heterogeneous fillers. This method aims to overcome the shortcomings of existing technologies when using diamond as a thermally conductive reinforcing filler for epoxy resin, thereby improving the thermal conductivity, insulation, heat resistance, and mechanical properties of the obtained epoxy insulation materials.
[0055] Specifically, a method for preparing a diamond-filled high thermal conductivity epoxy composite insulating material is proposed. The preparation method of this epoxy composite insulating material includes:
[0056] Prepare the following by weight percentage: 15-20% epoxy resin, 8-12% curing agent, 0.1-0.12% accelerator, 20-30% SiO2, 15-35% silica powder, 5-20% diamond, 1-10% light calcium carbonate, and 1-5% wollastonite; wherein the average particle size of SiO2, silica powder, and diamond is 10-20 μm, the average particle size of light calcium carbonate is 3-6 μm, and the average particle size of wollastonite is 10-38 μm with an aspect ratio of 10:1.
[0057] Purified diamond, SiO2, silica powder, light calcium carbonate, and wollastonite were obtained respectively.
[0058] Epoxy resin, curing agent, and accelerator accounting for 0.03% to 0.06% of the total mass of the obtained epoxy composite insulation material are placed in a reaction vessel and heated at a temperature of 60 to 100°C and a speed of 100 to 300 rpm with uniform stirring to obtain a homogeneous organic phase.
[0059] Obtaining the mixed phase: Purified SiO2, silica powder, light calcium carbonate, and wollastonite are added to the reactor in the following order: light calcium carbonate, SiO2, silica powder, and wollastonite. The feeding rate of light calcium carbonate, SiO2, silica powder, and wollastonite is 5-15 g / min (the next type of material is added only after the current material has been fed. For example, SiO2 is added immediately after all the light calcium carbonate has been fed). The mixture is heated and stirred at a uniform speed (heating temperature is 50-70℃, stirring speed is 500-800 rpm) to obtain a uniformly mixed phase.
[0060] Obtaining the target composite phase: Purified diamond was added to the mixed phase at a set rate (feeding rate 2-6 g / min), and the mixture was heated and stirred at a uniform speed (heating temperature 50-70℃, stirring speed 500-800 rpm) to obtain a homogeneous composite phase. The phase was then subjected to initial vacuum degassing (vacuum degree 0.08-0.1 MPa, degassing time 5-10 min). After vacuum degassing, the remaining accelerator was added to the composite phase, and a second vacuum degassing was performed (vacuum degree 0.08-0.1 MPa, degassing time 0.5-1 h) to obtain the target composite phase.
[0061] The target composite phase is vacuum cast (vacuum degree 0.08-0.1 MPa, vacuum casting temperature 60-100℃) followed by stepped curing (curing at 60-100℃ for 2-6 hours, then at 80-140℃ for 4-8 hours, and finally at 100-160℃ for 6-18 hours). After demolding, the target product (epoxy composite insulation material composed of multiple heterogeneous fillers) is obtained.
[0062] The above methods primarily regulate the crosslinking and curing rate and gel time of epoxy resin by altering the catalytic activity of the accelerator and optimizing the accelerator feeding process. Furthermore, leveraging the high density and low oil absorption characteristics of SiO2, silica powder, light calcium carbonate, and wollastonite, combined with the formulation of multi-component heterogeneous fillers, the intrinsic density difference between the resin matrix and diamond is reduced while ensuring the processability of the epoxy insulation material, thereby inhibiting diamond sedimentation within the resin matrix. Simultaneously, the close packing of the highly thermally conductive diamond with heterogeneous fillers of different particle sizes further enhances the thermal conductivity within the epoxy composite system. The strong interfacial interaction between the resin matrix and the inorganic fillers not only increases the crosslinking density of the composite network but also hinders the propagation of material cracks under external forces, thus achieving a synergistic improvement in the thermal conductivity, insulation, heat resistance, and mechanical properties of the epoxy composite material.
[0063] The specific steps for obtaining purified diamond powder, SiO2 powder, silica powder, light calcium carbonate powder, and wollastonite powder in the above method include:
[0064] Prepare five containers, each containing a mixed solution of ethanol and tetrahydrofuran;
[0065] Diamond, SiO2, silica powder, light calcium carbonate, and wollastonite were placed separately in a container.
[0066] Each container was subjected to reflux at a temperature of 60–80°C for 3–8 hours, during which the mixture in the container was stirred at a constant speed of 100–300 rpm. After reflux, solid-liquid phase separation was performed, and the separated material was placed in a constant temperature oven for continuous drying at a temperature of 60–150°C for 24–36 hours until the separated material particles were distinct, without accumulation or adhesion.
[0067] The purified diamond powder, SiO2 powder, silica powder, light calcium carbonate powder, and wollastonite powder were obtained.
[0068] To better understand the above technical solutions, the following will provide a detailed explanation of the technical solutions in conjunction with the accompanying drawings and specific embodiments.
[0069] Example 1
[0070] Step 1: Purification method using multi-component heterogeneous packing materials
[0071] Prepare five 1000mL containers and fill each container with a mixture of ethanol and tetrahydrofuran;
[0072] Diamond, SiO2, silica powder, light calcium carbonate, and wollastonite were placed separately in five of the aforementioned containers.
[0073] The mixture was stirred at 200 rpm for 6 hours at a constant temperature of 75℃. After stirring, solid-liquid phase separation was performed. The mixture was then dried in an oven at 100℃ for 24 hours until the inorganic powder particles were distinct and did not accumulate or adhere, thus obtaining the purified inorganic filler powder.
[0074] Step 2: Control of epoxy resin crosslinking and curing process and method of compounding multi-component heterogeneous fillers
[0075] 100g of E51 epoxy resin, 82.5g of hexahydrophthalic anhydride curing agent, and 0.05g of N,N-dimethylbenzylamine accelerator were weighed and placed into a mixing tank. The mixture was heated at a constant temperature of 80℃ and stirred at a constant speed of 200rpm to obtain a homogeneous organic phase.
[0076] Adjust the heating temperature to 60℃ and the stirring speed to 500 rpm. Add 50g of purified light calcium carbonate powder, 150g of SiO2, 200g of silica powder, and 15g of wollastonite to the organic phase in sequence, maintaining a feeding rate of 10g / min (add the light calcium carbonate first, then the silica powder, and so on). After continuous and uniform stirring, add 60g of purified diamond powder at a feeding rate of 5g / min, and stir uniformly to obtain a grayish-white organic-inorganic composite phase.
[0077] The obtained organic-inorganic composite phase was degassed under vacuum at 0.1 MPa for 1 h, and then 0.07 g of N,N-dimethylbenzylamine accelerator was added dropwise. The phase was then degassed again under vacuum at 0.1 MPa for 5 min to obtain the target composite phase.
[0078] Step 3: Preparation of multi-component heterogeneous filler compounded epoxy composite insulation material
[0079] Inside a vacuum casting machine, maintaining a vacuum casting temperature of 80℃ and a vacuum degree of 0.1 MPa, the obtained target composite phase was poured into a mold preheated to 80℃. After degassing for 5 minutes in the vacuum casting machine, step curing was performed. The step curing program was 80℃ / 2h, 120℃ / 4h, and 160℃ / 6h. After the curing program was completed, the mold was allowed to cool naturally to room temperature. The molded target product (epoxy composite insulation material with multiple heterogeneous fillers) sample was demolded and removed, and the material performance was tested.
[0080] Comparative Example 1
[0081] Preparation of unfilled epoxy insulation material samples
[0082] 100g of epoxy resin, 82.5g of hexahydrophthalic anhydride curing agent, and 0.12g of N,N-dimethylbenzylamine accelerator were taken and heated at 80℃ and stirred at 200rpm to obtain a homogeneous organic phase. The mixture was then degassed under a vacuum of 0.1MPa for 1 hour, followed by another 5 minutes of degassed treatment at 0.1MPa. The resulting liquid was then poured into a preheated mold at 80℃ using a vacuum casting machine, maintaining the vacuum casting temperature at 80℃ and the vacuum at 0.1MPa. After 5 minutes of degassed treatment, a stepped curing process was performed. The stepped curing program was 80℃ / 2h, 120℃ / 4h, and 160℃ / 6h. After curing, the mold was allowed to cool naturally to room temperature. The unfilled epoxy insulation material sample was then demolded and removed for performance testing.
[0083] Comparative Example 2
[0084] Preparation of diamond / epoxy composite insulation material samples
[0085] 100g of epoxy resin, 82.5g of hexahydrophthalic anhydride curing agent, and 0.12g of N,N-dimethylbenzylamine accelerator were taken and heated at 80℃ and stirred at 200rpm to obtain a homogeneous organic phase. 60g of diamond powder was added to the organic phase at a feeding rate of 5g / min and stirred at 500rpm until homogeneous. The mixture was then degassed under a vacuum of 0.1MPa for 1 hour. The resulting liquid was then poured into a mold preheated to 80℃ using a vacuum casting machine. The vacuum casting temperature was maintained at 80℃ and the vacuum degree at 0.1MPa. After degassed for 5 minutes, step curing was performed. The step curing program was 80℃ / 2h, 120℃ / 4h, and 160℃ / 6h. After curing, the mold was allowed to cool naturally to room temperature. The unfilled epoxy insulation material sample was demolded and removed, and its sedimentation coefficient was tested.
[0086] Comparative Example 3
[0087] Preparation of multi-component heterogeneous filler composite epoxy insulation material samples under different filler feeding sequences
[0088] 100g of E51 epoxy resin, 82.5g of hexahydrophthalic anhydride curing agent, and 0.05g of N,N-dimethylbenzylamine accelerator were weighed separately and heated at 80℃ and stirred at 200rpm to obtain a homogeneous organic phase. The heating temperature was adjusted to 60℃ and the stirring speed to 500rpm. The purified filler from Example 1 was added to the organic phase in the following order, maintaining a mixing rate of 10g / min:
[0089] ①15g wollastonite, 200g silica powder, 150g SiO2, 50g light calcium carbonate;
[0090] ②200g silica powder, 150g SiO2, 50g light calcium carbonate, 15g wollastonite;
[0091] ③ 50g light calcium carbonate, 15g wollastonite, 150g SiO2, 200g silica powder;
[0092] After continuous and uniform stirring, 60g of diamond powder was added at a feeding rate of 5g / min, and the mixture was stirred at a uniform speed to obtain a grayish-white organic-inorganic composite phase. The mixture was then degassed under a vacuum of 0.1 MPa for 1 hour. Next, 0.07g of N,N-dimethylbenzylamine accelerator was added dropwise, and the mixture was degassed under vacuum for 5 minutes. In a vacuum casting machine, maintaining a vacuum casting temperature of 80℃ and a vacuum of 0.1 MPa, the uniformly mixed liquid was poured into a mold preheated to 80℃. After degassed under vacuum for 5 minutes, step curing was performed at 80℃ for 2 hours, 120℃ for 4 hours, and 160℃ for 6 hours. After curing, the mold was allowed to cool naturally to room temperature. The cured multi-component heterogeneous filler composite epoxy composite insulation material sample was then demolded and removed for performance testing and characterization.
[0093] Comparative Example 4
[0094] Preparation of multi-component heterogeneous filler composite epoxy composite insulation material samples under different types of accelerators and feeding processes
[0095] 100g of E51 epoxy resin, 82.5g of hexahydrophthalic anhydride curing agent, and a certain amount of accelerator were weighed and heated at 80℃ and stirred at 200rpm to obtain a homogeneous organic phase. The heating temperature was adjusted to 60℃ and the stirring speed to 500rpm. 50g of purified light calcium carbonate powder, 150g of SiO2, 200g of silica powder, and 15g of wollastonite from Example 1 were added to the organic phase in sequence at a feeding rate of 10g / min. After continuous uniform stirring, 60g of diamond powder was added at a feeding rate of 5g / min, and the mixture was stirred uniformly to obtain a grayish-white organic-inorganic composite phase. The phase was degassed under a vacuum of 0.1MPa for 1 hour. A certain amount of accelerator was added again, and the phase was degassed under vacuum for 5 minutes. Inside a vacuum casting machine, maintaining a vacuum casting temperature of 80℃ and a vacuum degree of 0.1 MPa, the uniformly mixed molten material was poured into a mold preheated to 80℃. After degassing for 5 minutes in the vacuum casting machine, step curing was performed. The step curing program was 80℃ / 2h, 120℃ / 4h, and 160℃ / 6h. After the curing program was completed, the mold was allowed to cool naturally to room temperature. The molded and cured multi-component heterogeneous filler composite epoxy composite insulation material sample was then removed and its performance was characterized.
[0096] The preparation process of the above-mentioned epoxy composite insulation material samples was repeated seven times, with the main steps being the same each time. The difference lay in the type of accelerator added in the first and second stages of each preparation process, which were as follows:
[0097] ① First, add 0.07g of a mixed accelerator of aromatic amines and fatty amines, and then add 0.05g of the same accelerator in the second step;
[0098] ② First, add 0.07g of imidazole and salt accelerator (2-ethyl-4-methylimidazolium), then add 0.05g of the same accelerator in the second addition;
[0099] ③ First, add 0.07g of a substituted urea accelerator (N-(2-hydroxyphenyl)-N',N'-dimethylurea), and then add 0.05g of the same accelerator in the second step;
[0100] ④ The first time, 0.12g of N,N-dimethylbenzylamine accelerator was added directly, but no accelerator was added the second time;
[0101] ⑤ Add 0.03g of N,N-dimethylbenzylamine accelerator for the first time, and then add 0.09g of N,N-dimethylbenzylamine accelerator for the second time;
[0102] ⑥ Add 0.08g of N,N-dimethylbenzylamine accelerator for the first time, and then add 0.04g of N,N-dimethylbenzylamine accelerator for the second time;
[0103] ⑦ No accelerator was added the first time, but 0.12g of N,N-dimethylbenzylamine accelerator was added the second time.
[0104] Seven samples were obtained, and the material properties were characterized by testing.
[0105] Example 2
[0106] 100g of E51 epoxy resin, 82.5g of hexahydrophthalic anhydride curing agent, and 0.05g of N,N-dimethylbenzylamine accelerator were weighed separately and heated at 80℃ and stirred at 200rpm to obtain a homogeneous organic phase. The heating temperature was adjusted to 60℃ and the stirring speed to 500rpm. 70g of light calcium carbonate, 130g of SiO2, 190g of silica powder, and 25g of wollastonite were added to the organic phase in sequence at a mixing rate of 10g / min. After continuous uniform stirring, 60g of diamond powder was added at a feeding rate of 5g / min, and the mixture was stirred uniformly to obtain a grayish-white organic-inorganic composite phase. The phase was then degassed under a vacuum of 0.1MPa for 1h. Then, 0.07g of N,N-dimethylbenzylamine accelerator was added dropwise, and the phase was degassed under vacuum for 5min. Inside a vacuum casting machine, under a vacuum casting temperature of 80℃ and a vacuum degree of 0.1 MPa, the uniformly mixed molten material was poured into a mold preheated to 80℃. After degassing for 5 minutes in the vacuum casting machine, step curing was performed. The step curing program was 80℃ / 3h, 130℃ / 3h, and 160℃ / 6h. After the curing program was completed, the mold was allowed to cool naturally to room temperature. The molded and cured multi-component heterogeneous filler composite epoxy composite insulation material sample was then removed and its performance was characterized.
[0107] Example 3
[0108] 100g of E51 epoxy resin, 82.5g of hexahydrophthalic anhydride curing agent, and 0.05g of N,N-dimethylbenzylamine accelerator were weighed separately and heated at 80℃ and stirred at 200rpm to obtain a homogeneous organic phase. The heating temperature was adjusted to 60℃ and the stirring speed to 500rpm. 90g of light calcium carbonate, 110g of SiO2, 180g of silica powder, and 35g of wollastonite were added to the organic phase in sequence at a mixing rate of 15g / min. After continuous uniform stirring, 60g of diamond powder was added at a feeding rate of 8g / min, and the mixture was stirred uniformly to obtain a grayish-white organic-inorganic composite phase. The phase was then degassed under a vacuum of 0.1MPa for 1 hour. Then, 0.07g of N,N-dimethylbenzylamine accelerator was added dropwise, and the phase was degassed under vacuum for 5 minutes. Inside a vacuum casting machine, under a vacuum casting temperature of 80℃ and a vacuum degree of 0.1 MPa, the uniformly mixed molten material was poured into a mold preheated to 80℃. After degassing for 5 minutes in the vacuum casting machine, step curing was performed. The step curing program was 80℃ / 3h, 130℃ / 5h, and 160℃ / 5h. After the curing program was completed, the mold was allowed to cool naturally to room temperature. The molded and cured multi-component heterogeneous filler composite epoxy composite insulation material sample was then removed and its performance was characterized.
[0109] Example 4
[0110] 100g of E51 epoxy resin, 82.5g of hexahydrophthalic anhydride curing agent, and 0.05g of N,N-dimethylbenzylamine accelerator were weighed separately and heated at 80℃ and stirred at 200rpm to obtain a homogeneous organic phase. The heating temperature was adjusted to 60℃ and the stirring speed to 500rpm. 40g of light calcium carbonate, 160g of SiO2, 205g of silica powder, and 10g of wollastonite were added to the organic phase in sequence at a mixing rate of 20g / min. After continuous uniform stirring, 60g of diamond powder was added at a feeding rate of 10g / min, and the mixture was stirred uniformly to obtain a grayish-white organic-inorganic composite phase. The phase was then degassed under a vacuum of 0.1MPa for 1h. Then, 0.07g of N,N-dimethylbenzylamine accelerator was added dropwise, and the phase was degassed under vacuum for 5min. Inside a vacuum casting machine, under a vacuum casting temperature of 80℃ and a vacuum degree of 0.1 MPa, the uniformly mixed molten material was poured into a mold preheated to 80℃. After degassing for 5 minutes in the vacuum casting machine, step curing was performed. The step curing program was 80℃ / 4h, 130℃ / 6h, and 160℃ / 6h. After the curing program was completed, the mold was allowed to cool naturally to room temperature. The molded and cured multi-component heterogeneous filler composite epoxy composite insulation material sample was then removed and subjected to performance testing and characterization.
[0111] Example 5
[0112] 100g of E51 epoxy resin, 82.5g of hexahydrophthalic anhydride curing agent, and 0.05g of N,N-dimethylbenzylamine accelerator were weighed separately and heated at 80℃ and stirred at 200rpm to obtain a homogeneous organic phase. The heating temperature was adjusted to 60℃ and the stirring speed to 500rpm. 30g of light calcium carbonate, 170g of SiO2, 210g of silica powder, and 5g of wollastonite were added to the organic phase in sequence at a mixing rate of 25g / min. After continuous uniform stirring, 60g of diamond powder was added at a feeding rate of 10g / min, and the mixture was stirred uniformly to obtain a grayish-white organic-inorganic composite phase. The phase was then degassed under a vacuum of 0.1MPa for 1h. Then, 0.07g of N,N-dimethylbenzylamine accelerator was added dropwise, and the phase was degassed under vacuum for 5min. Inside a vacuum casting machine, under a vacuum casting temperature of 80℃ and a vacuum degree of 0.1 MPa, the uniformly mixed molten material was poured into a mold preheated to 80℃. After degassing for 5 minutes in the vacuum casting machine, step curing was performed. The step curing program was 80℃ / 4h, 130℃ / 6h, and 160℃ / 6h. After the curing program was completed, the mold was allowed to cool naturally to room temperature. The molded and cured multi-component heterogeneous filler composite epoxy composite insulation material sample was then removed and subjected to performance testing and characterization.
[0113] The method of testing in this application's embodiments or comparative examples is as follows:
[0114] Thermal conductivity test: The thermal conductivity of the sample was tested using a laser thermal conductivity meter LFA457 according to the national standard GB / T 22588-2008 "Measurement of thermal diffusivity or thermal conductivity by flash method". The test sample was a circular disc with a diameter of 12.7 cm and a thickness of 1 mm, and the test temperature was 25℃.
[0115] AC breakdown strength test: According to the national standard GB / T 1408.1-2016 "Test Method for Electrical Strength of Insulating Materials", the breakdown strength of the samples under short-time electric field was measured at a voltage increase rate of 2kV / s. The ambient temperature was 25℃. The test specimen was a circular disc with a diameter of 100mm and a thickness of 1mm. The test voltage frequency was 50Hz. Three finished products of each type of sample were taken, and three points were tested on each sample, resulting in nine breakdown data points for each type of sample. The test results were averaged, and the breakdown strength was calculated using the Weibull distribution.
[0116] Flexural strength test: According to the national standard GB / T2567-2008 "Test Methods for Properties of Resin Castings", a universal testing machine was used to measure the elastic modulus and flexural strength of the specimens. The test specimens were cast according to the technical conditions specified in GB / T2567-2008. The test temperature was 25℃, and the ambient humidity was 50%RH. The test speed was 10 mm / min for flexural strength measurement and 2 mm / min for elastic modulus measurement. The arbitration test speed was 2 mm / min. Each type of specimen was tested three times, and the average value was taken.
[0117] Glass transition temperature test: The glass transition temperature of the samples was tested using a differential scanning calorimeter according to the national standard DB44 / T 2045-2017 "Determination of Glass Transition Temperature of Synthetic Resin Emulsions". The test conditions were a nitrogen atmosphere, with a heating rate of 10℃ / min, from room temperature to 250℃, followed by cooling to room temperature and then heating back to 250℃ at the same rate to obtain the test results.
[0118] Power frequency dielectric loss test: According to the national standard GB / T1409-2006 "Recommended methods for measuring the permittivity and dielectric loss factor of electrical insulating materials at power frequency, audio frequency, and high frequency", the dielectric constant and dielectric loss of the sample were tested using a dielectric property tester. The test sample was a circular disc with a diameter of 100 mm and a thickness of 1 mm. The test frequency was 50 Hz, the temperature was 25℃, and the voltage was 1 kV. Each sample was tested 8 times, and the average value of the test results was taken.
[0119] Viscosity-time curve test of epoxy resin composite: According to the national standard GB / T 22314-2008 "Standard for Determination of Viscosity of Epoxy Resins in Plastics", a rotational viscometer was used for testing. The test temperature was 80℃. The viscosity of the epoxy resin composite was measured as a function of time, and the initial viscosity value was established. The viscosity curve of the epoxy composite material was then plotted.
[0120] Epoxy Resin Composite Sedimentation Coefficient Test: According to the national standard GB12007.5-89 "Determination of Density of Epoxy Resin - Specific Gravity Bottle Method", the sedimentation coefficient of the epoxy resin composite is tested using the specific gravity method. Take approximately 10mm from the top and bottom of the resin sample and measure the density (specific gravity). Let k be the sedimentation coefficient, then:
[0121]
[0122] Where ρ 上 ρ represents the top density (specific gravity). 下 The bottom density (specific gravity) is the value of the packing material. The closer the settling coefficient of the packing material is to 1, the less obvious the settling of the packing material is, meaning that the method has a better effect on inhibiting the settling of the packing material.
[0123] The test results obtained are as follows Figure 1-12 Among them, the unfilled epoxy insulation material is the epoxy insulation material sample prepared in Comparative Example 1, the diamond / epoxy composite insulation material is the epoxy composite insulation material prepared in Comparative Example 2, and the multi-component heterogeneous filler compounded epoxy composite insulation material is the target product obtained in Example 1.
[0124] like Figure 1 As can be seen from the figure, in the epoxy composite insulation material obtained in Example 1, the compatibility between the filler and the resin matrix is good, and no obvious defects or pores are found. This is the main reason for the improved performance of the compounded epoxy composite insulation material compared with the unfilled epoxy insulation material.
[0125] like Figure 2 As shown in the figure, the thermal conductivity of the sample obtained in Example 1 reaches 1.045 W / m·K, which is 383% higher than the thermal conductivity of 0.216 W / m·K of the unfilled epoxy insulation material (Comparative Example 1). By testing the thermal conductivity at the bottom filler settlement point of the diamond / epoxy composite insulation material (Comparative Example 2), it can be found that its thermal conductivity is 0.621 W / m·K, only 60% of the thermal conductivity of the epoxy composite insulation material obtained in Example 1. Therefore, it can be concluded that the multi-component heterogeneous filler composed of diamond, SiO2, silica powder, light calcium carbonate, and wollastonite forms a continuous thermal conductivity pathway within the epoxy resin, resulting in the better thermal conductivity of the epoxy composite insulation material after filler compounding.
[0126] like Figure 3The AC breakdown strength of the material obtained in Example 1 increased from 36.08 kV / mm without filler to 39.69 kV / mm, an increase of nearly 10%. This demonstrates that the filling with multi-component heterogeneous fillers can effectively enhance the insulation performance of epoxy materials, thereby improving their operational reliability in electronic devices and power equipment. In contrast, the AC breakdown strength of the diamond / epoxy composite insulation material was only 32.32 kV / mm, which also verifies that the settling of diamond filler leads to a decrease in the insulation performance of the epoxy composite material.
[0127] like Figure 4 The order in which multi-component heterogeneous fillers are added affects the AC breakdown strength of epoxy composite insulation materials. In Example 1, the AC breakdown strength of the composite material obtained by adding light calcium carbonate, SiO2, silica powder and wollastonite in the order of addition is significantly better than that of the filler addition order shown in Comparative Example 3.
[0128] like Figure 5 The glass transition temperature of the epoxy composite insulation material with multi-component heterogeneous fillers increased from 131℃ to 136℃, indicating that the increased cross-linking density of the composite system effectively enhanced the thermal properties of the material and further expanded its service life. However, the glass transition temperature of the diamond / epoxy composite insulation material decreased from 131℃ to 128℃, which also verifies that filler sedimentation causes a decrease in the cross-linking density of the epoxy cross-linking network, leading to a decline in the thermal properties of the composite insulation material.
[0129] like Figure 6 The flexural strength of epoxy composite insulation material with multi-component heterogeneous fillers increased from 115 MPa in the unfilled form to 131 MPa, an increase of 12.2%. This indicates that multi-component heterogeneous filler formulation can effectively enhance the mechanical properties of epoxy composite materials, thereby meeting the operational requirements of materials in electronic devices and power equipment. However, the flexural strength of diamond / epoxy composite insulation material decreased from 115 MPa to 98 MPa. This indicates that uneven dispersion of diamond within the resin matrix hinders local cross-linking of the resin, leading to relative stress concentration in localized areas of the composite material and a significant decrease in the mechanical properties of the diamond / epoxy composite insulation material.
[0130] like Figure 7 The order in which the multi-component heterogeneous fillers are added also affects the mechanical properties of epoxy composite insulation materials. For example, when the fillers are added according to the three order in Comparative Example 3, the flexural strength of the composite material is only 104 MPa, 106 MPa, and 110 MPa. Compared with the epoxy composite insulation material prepared in Example 1, the mechanical properties are significantly reduced.
[0131] like Figure 8The power frequency dielectric loss of epoxy composite insulation materials with multi-component heterogeneous fillers decreased from 0.502% to 0.213%, a reduction of 135%. Diamond / epoxy composite insulation materials also showed a certain reduction in power frequency dielectric loss, but the decrease was smaller. This indicates that epoxy composite insulation materials result in lower energy loss in electronic devices and power equipment, and generate less heat due to dielectric loss, thus helping to ensure higher operating efficiency and longer service life for electronic devices and power equipment.
[0132] like Figure 9 The viscosity of the epoxy composite insulation material with multi-component heterogeneous fillers increased compared to the unfilled epoxy insulation material, rising from 100–5500 MPa·s to 3100–8700 MPa·s. This increased hysteresis resistance experienced by the fillers during resin sedimentation effectively reduced the sedimentation of high-density fillers within the resin matrix. Simultaneously, the gel time of the two materials only changed from 452 min to 418 min, showing no significant change. This indicates that the combination of multi-component heterogeneous fillers does not significantly alter the processing performance of the epoxy composite insulation material. This demonstrates that this method can achieve a synergistic improvement in the multi-dimensional service performance of epoxy insulation materials while ensuring their processing performance.
[0133] from Figure 10 As can be seen from Comparative Examples 4①, ②, and ③, by selecting different types of accelerators to change their catalytic activity, the processing performance of epoxy composite materials can be optimized, which also provides a possibility for suppressing the sedimentation of fillers in the resin matrix. Among them, imidazole and its salts and substituted urea accelerators have excessively long gel times (all exceeding 1000 min), and the viscosity of the composite material increases relatively slowly (at 1000 min, the viscosity of the composite material is still below 5000 mPa·s). This also leads to a prolonged sedimentation time of the filler in the resin matrix, exacerbating the sedimentation of fillers in the epoxy composite material, and therefore is not suitable as epoxy accelerators in this method. Amine accelerators, on the other hand, have moderate activity, which allows them to impart suitable curing rates (gel times greater than 400 min) and viscosities to the material (the viscosity of the composite material can reach 5500 mPa·s at 500 min), and can play a good role in suppressing the sedimentation of fillers in epoxy composite materials.
[0134] In general, to meet the curing and molding requirements of epoxy insulation materials, the gel time should not be too long or too short. Therefore, this patent, by regulating the catalytic activity of the epoxy accelerator, can suppress the sedimentation of fillers in the epoxy resin matrix while ensuring the process performance of the epoxy material.
[0135] from Figure 11It can be seen that the flexural strength of the epoxy composite insulation material samples with multi-component heterogeneous fillers in Examples 1-5 exhibits certain fluctuations with changes in the filler component ratio. The flexural strength of the epoxy composite insulation materials remains around 130 MPa, with the highest flexural strength of 138 MPa observed in Example 3. Overall, the method of compounding with multi-component heterogeneous fillers can significantly improve the mechanical properties of epoxy composite insulation materials, enabling them to meet the service requirements in power equipment and electronic devices.
[0136] from Figure 12 It can be seen that changing the ratio of filler components in Examples 1-5 affects the insulation performance of the epoxy composite material after curing. Among them, the AC breakdown strength of the epoxy composite insulation material prepared in Example 3 can reach 40.29 kV / mm, and the AC breakdown strength of the samples in the other examples is all above 39 kV / mm. Therefore, the epoxy composite insulation materials obtained by this method all have AC insulation capabilities, which can greatly improve the reliability of safe and stable operation of power equipment.
[0137] from Figure 13 It can be seen that the type and order of addition of the accelerators in Comparative Examples 4① to 7 also affect the mechanical properties of the epoxy insulation materials after curing. As shown in Comparative Examples 4① to ③, when amine-based mixed accelerators, imidazole and salt-based accelerators, and substituted urea-based accelerators were selected respectively, the flexural strength of the epoxy composite insulation materials decreased from 127 MPa to 104 MPa, and the mechanical properties of the materials decreased significantly. Meanwhile, when the order of addition of the accelerators was changed (as shown in Comparative Examples 4④ to ⑦), the flexural strength of the epoxy composite insulation materials ranged from a maximum of 120 MPa to a minimum of only 85 MPa. This is basically consistent with the variation law of the settling coefficient of the filler in the epoxy composite insulation materials, thus verifying that the accelerator affects the settling of the filler in the composite material, thereby changing the mechanical properties of the composite material after curing.
[0138] Table 1. Filler settling coefficient of epoxy composite insulation material with multi-component heterogeneous fillers.
[0139]
[0140] The sedimentation coefficient reflects the sedimentation of the filler in the organic phase. When the sedimentation coefficient of the composite material is closer to 1, it indicates that the sedimentation of the filler in the organic phase is less obvious.
[0141] As shown in Table 1, compared with the single-filler diamond / epoxy composite insulation material, the sedimentation coefficient of the multi-component heterogeneous filler composite epoxy composite insulation material has been significantly improved, increasing from 0.3715 to 0.9405. This verifies the outstanding effect of this method in suppressing the sedimentation of fillers in the organic phase.
[0142] Secondly, by adjusting the catalytic activity of the accelerators, the catalytic effect of different types of accelerators on the crosslinking reaction of epoxy resin was investigated. It was found that the catalytic activity of the accelerators affects the sedimentation coefficient of the fillers in the composite material. For example, when N,N-dimethylbenzylamine with high catalytic activity was selected in Example 1, the sedimentation coefficient of the obtained sample was higher, indicating that the accelerator has a good inhibitory effect on the sedimentation of the fillers in the composite material.
[0143] Meanwhile, changing the order in which accelerators are added also affects the settling of fillers within the composite material. For example, in Comparative Example 4①, the excessive amount of accelerator added initially caused the viscosity of the composite material to rise rapidly, making it impossible to accurately measure the density within the composite material. In Comparative Example 4⑦, however, the viscosity of the composite material rose slowly without the addition of accelerators, resulting in a lower settling coefficient. This reflects the crucial importance of regulating the crosslinking reaction process of the resin, curing agent, and accelerator in suppressing filler settling.
[0144] Furthermore, the order in which the multi-component heterogeneous fillers are added within the organic phase also affects the settling coefficient of the fillers in the composite material. It can be found that the order in which lightweight calcium carbonate, SiO2, silica fume, wollastonite, and diamond are added can achieve a better effect on suppressing filler settling, thus verifying the rationality of the order in which the multi-component heterogeneous fillers are added.
[0145] As the proportions of SiO2, silica fume, light calcium carbonate, wollastonite, and diamond filler in the epoxy resin change, the settling coefficient and density of the epoxy composite insulation material will also change accordingly. Furthermore, in Example 3, the filler settling coefficient in the composite material reached 0.9817, indicating that this method can exhibit a good effect in inhibiting filler settling.
[0146] The diamond, SiO2, silica powder, light calcium carbonate, and wollastonite involved in the aforementioned embodiments and comparative examples are hexagonal diamond, spherical SiO2, amorphous silica powder, amorphous light calcium carbonate, and wollastonite, respectively. Some of the physicochemical properties of the above materials are shown in Table 2.
[0147] Table 2 lists some of the physicochemical properties of the multi-component heterogeneous packings used.
[0148]
[0149] In this application, SiO2 and silicon micropowder, while possessing excellent properties such as high chemical stability and low dielectric constant, have been widely used as reinforcing fillers for epoxy resins used in integrated circuit packaging. However, the intrinsic thermal conductivity of SiO2 and silicon micropowder is low, only 15–25 W / m·K. High proportions of SiO2 and silicon micropowder filling not only lead to a decrease in the processing performance of epoxy insulation materials, but their effect on improving the thermal conductivity of epoxy insulation materials is often not significant. For example, the high thermal conductivity electronic packaging bottom filler adhesive based on multi-component filler compound disclosed in Chinese Patent Publication No. CN 104910845A, although capable of increasing the thermal conductivity of epoxy packaging materials to over 1 W / m·K, the high proportion of unmodified nanofillers causes a sharp increase in material viscosity. Furthermore, the addition of various epoxy additives such as diluents, dispersants, and toughening agents leads to an imbalance between the insulation and heat resistance properties of the composite material. The mutual coupling and constraints between these multi-dimensional properties will significantly limit the application of this epoxy packaging material in the field of electrical insulation.
[0150] To overcome the shortcomings of using diamond as a filler in epoxy insulating and thermally conductive materials, this application proposes a method for preparing a high thermal conductivity epoxy composite insulating material reinforced by a composite filler consisting of diamond, SiO2, silica powder, light calcium carbonate, and wollastonite. Specifically, this method primarily controls the cross-linking and curing reaction rate and gel time of the epoxy resin by altering the catalytic activity of the accelerator and optimizing the accelerator feeding process. Furthermore, it utilizes the high density and low oil absorption characteristics of active SiO2, silica powder, amorphous light calcium carbonate, and fibrous wollastonite inorganic fillers, combined with the composite filler composition, to reduce the intrinsic density difference between the resin matrix and diamond while ensuring the processability of the epoxy insulating material, thereby inhibiting diamond sedimentation within the resin matrix. Simultaneously, the close packing of the highly thermally conductive diamond with the heterogeneous fillers of different particle sizes further enhances the thermal conductivity within the epoxy composite system. The strong interfacial interaction between the resin matrix and the inorganic filler not only increases the crosslinking density of the composite network, but also hinders the propagation of material cracks under external force, thereby achieving a synergistic improvement in the thermal conductivity, insulation, heat resistance and mechanical properties of epoxy composite insulation materials.
[0151] In summary, the epoxy composite insulation material prepared by the method proposed in this application exhibits a significantly improved sedimentation coefficient compared to unfilled epoxy insulation material. The thermal conductivity of the composite material also increases from 0.216 W / m·K to 1.045 W / m·K, an increase of 383%. The AC breakdown strength increases from 36.08 kV / mm to 39.69 kV / mm, an increase of nearly 10%. The glass transition temperature rises from 131℃ to 136℃, an increase of 3.8%. The flexural strength increases from 115 MPa to 131 MPa, an increase of 12.2%. Furthermore, the dielectric loss of the epoxy composite insulation material at power frequency decreases from 0.502% to 0.213%, thus achieving a synergistic enhancement of the multi-dimensional properties of the epoxy insulation material.
[0152] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0153] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a diamond-filled high thermal conductivity epoxy composite insulating material, characterized in that, The method includes: Prepare the following by weight percentage: 15-20% epoxy resin, 8-12% curing agent, 0.1-0.12% accelerator, 20-30% SiO2, 15-35% silica powder, 5-20% diamond, 1-10% light calcium carbonate and 1-5% wollastonite. Purified diamond, SiO2, silica powder, light calcium carbonate, and wollastonite were obtained respectively. Obtaining the organic phase: Place epoxy resin, curing agent and part of the accelerator in a reaction vessel, heat and stir at a uniform speed to obtain a homogeneous organic phase; Obtaining the mixed phase: Purified SiO2, silica powder, light calcium carbonate and wollastonite are added to the reactor in the set order and speed, heated and stirred at a uniform speed to obtain a homogeneous mixed phase; Obtaining the target composite phase: Purified diamond is added to the mixed phase at a set rate, heated and stirred at a uniform speed to obtain a homogeneous composite phase, and then subjected to initial vacuum degassing. After vacuum degassing is completed, the remaining accelerator is added to the composite phase, and a second vacuum degassing is performed to obtain the target composite phase. The target composite phase was vacuum cast and then cured in stages. After demolding, the target product was obtained. The specific order of feeding SiO2, silica fume, light calcium carbonate, and wollastonite during the process of obtaining the mixed phase is as follows: light calcium carbonate, SiO2, silica fume, and wollastonite, with the feeding rates of light calcium carbonate, SiO2, silica fume, and wollastonite all being 5~15 g / min; The epoxy resin matrix is one or more of glycidyl ethers, glycidyl esters, glycidyl amines, linear aliphatic resins, and alicyclic resins; The curing agent is hexahydrophthalic anhydride; The accelerator is N,N-dimethylbenzylamine.
2. The method for preparing a diamond-filled high thermal conductivity epoxy composite insulating material according to claim 1, characterized in that, The process of obtaining purified diamond powder, SiO2 powder, silica powder, light calcium carbonate powder, and wollastonite powder includes: Prepare five containers, each containing a mixed solution of ethanol and tetrahydrofuran; Diamond, SiO2, silica powder, light calcium carbonate, and wollastonite are each placed in one of the containers. Each container is subjected to reflux at a temperature of 60-80°C for 3-8 hours. During the reflux process, the mixture in the container is stirred at a constant speed of 100-300 rpm. After reflux, solid-liquid phase separation is performed, and the separated material is placed in a constant temperature oven for continuous drying at a temperature of 60-150°C for 24-36 hours until the separated material particles are distinct, do not accumulate, and do not adhere. The purified diamond powder, SiO2 powder, silica powder, light calcium carbonate powder, and wollastonite powder were obtained.
3. The method for preparing a diamond-filled high thermal conductivity epoxy composite insulating material according to claim 1, characterized in that, The process involves placing epoxy resin, curing agent, and a portion of the accelerator in a reaction vessel, heating and stirring at a uniform speed to obtain a homogeneous organic phase. Specifically: Epoxy resin, curing agent, and accelerator accounting for 0.03%~0.06% of the total mass of the target product are placed in a reaction vessel and heated at a temperature of 60~100℃ and a speed of 100~300rpm with uniform stirring to obtain a homogeneous organic phase.
4. The method for preparing a diamond-filled high thermal conductivity epoxy composite insulating material according to claim 1, characterized in that, During the process of obtaining the mixed phase and the target composite phase, the heating and uniform stirring conditions are: heating temperature of 50~70℃ and stirring speed of 500~800rpm.
5. The method for preparing a diamond-filled high thermal conductivity epoxy composite insulating material according to claim 1, characterized in that, The vacuum degree of both the primary and secondary vacuum degassing is 0.08~0.1 MPa. The degassing time of the primary vacuum degassing is 0.5~1 h, and the degassing time of the secondary vacuum degassing is 5~10 min.
6. The method for preparing a diamond-filled high thermal conductivity epoxy composite insulating material according to claim 1, characterized in that, The vacuum casting conditions are: vacuum degree of 0.08~0.1Mpa, vacuum casting temperature of 60~100℃; the step curing is specifically: curing treatment at 60~100℃ for 2~6h, then curing treatment at 80~140℃ for 4~8h, and finally curing treatment at 100~160℃ for 6~18h.
7. The method for preparing a diamond-filled high thermal conductivity epoxy composite insulating material according to claim 1, characterized in that, The diamond feeding rate during the acquisition of the target composite phase is 2~6 g / min.
8. The method for preparing a diamond-filled high thermal conductivity epoxy composite insulating material according to claim 1, characterized in that, The average particle size of SiO2, silica powder and diamond is 10~20 μm, the average particle size of light calcium carbonate is 3-6 μm, and the average particle size of wollastonite is 10~38 μm with an aspect ratio of 10:1.
Citation Information
Patent Citations
Underfill adhesive and preparation method thereof
CN104910845A
Nano diamond heat-dissipation and energy-saving environment-friendly thin film paint and preparation and application methods of nano diamond heat-dissipation and energy-saving environment-friendly thin film paint
CN106752645A
Nano diamond / epoxy resin composite and preparation method thereof
CN107446308A
Epoxy resin composition, preparation method thereof and plugging aluminum plate
CN103709605A
Epoxy resin composite material for packaging power electronic transformer and preparation method of composite material
CN113881190A